Natural Potent NAAA Inhibitor Atractylodin Counteracts LPS-Induced Microglial Activation - Yang, Longhe; Ji, Chunyan; Li, Yitian; Hu, Fan; Zhang, Fang; Zhang, Haiping; Li, Long; Ren, Jie; Wang, Zhaokai; Qiu, Yan (Frontiers in Pharmacology, 2020)
N-acylethanolamine-hydrolyzing acid amidase (NAAA) is a lysosomal enzyme that inhibits the degradation of palmitoylethanolamide (PEA), an endogenous lipid that induces analgesic, anti-inflammation, and anti-multiple sclerosis through PPARα activation. Only a few potent NAAA inhibitors have been reported to date, which is mainly due to the restricted substrate-binding site of NAAA. Here, we established a high-throughput fluorescence-based assay for NAAA inhibitor screening. Several new classes of NAAA inhibitors were discovered from a small library of natural products. One of these is atractylodin, a polyethylene alkyne compound from the root of Atractylodes lancea (Thunb) DC., which significantly inhibits NAAA activity and has an IC50 of 2.81 µM. Kinetic analyses and dialysis assays suggested that atractylodin engages in competitive inhibition via reversible reaction to the enzyme. Docking assays revealed that atractylodin occupies the catalytic cavity of NAAA, where the atractylodin furan head group has a hydrophobic-related interaction with the backbone of the Trp181 and Leu152 residues of human NAAA. Further investigation indicated that atractylodin significantly increases PEA and OEA levels and dose-dependently inhibits LPS-induced nitrate, TNF-α, IL-1β, and IL-6 pro-inflammatory cytokine release in BV-2 microglia. Our results show that atractylodin elevates cellular PEA levels and inhibits microglial activation by inhibiting NAAA activity, which in turn could contribute to NAAA functional research.